Temporally resolved single-cell RNA sequencing reveals protective and pathological responses during herpes simplex virus CNS infection - Xiangning Ding; Xin Lai; Ida H. Klaestrup; Sara R. N. Jensen; Morten M. Nielsen; Kasper Thorsen; Marina Romero-Ramos; Yonglun Luo; Lin Lin; Line S. Reinert; Søren R. Paludan (Journal of Neuroinflammation)
Abstract Background Herpes Simplex Virus 1 (HSV-1) is a neurotropic virus causing encephalitis and post-infectious complications. Infections can induce a range of acute, subacute, and progressing brain disease, and in recent years it has emerged that immune responses are involved in the pathogenesis of these diseases. Methods Mice were infected with HSV-1 through corneal infection, and the brain stem was analyzed using single-cell and GeoMx spatial transcriptomics. Through these technologies we profiled temporal transcriptomic changes in cell populations, pathways, and cell-cell communication associated with antiviral activity and inflammation-induced disturbance of physiological brain structures and activities. Results We found that microglia proportions increased early after HSV-1 infection, followed by monocyte influx and later by T cells. The blood-brain barrier was disrupted, and transcriptomic profiles associated with homeostatic brain transcriptional activities were altered. Early transcriptional responses were dominated by antiviral and inflammatory activities. A microglia subpopulation with high type I interferon and chemokine expression localized to infection sites, likely mediating antiviral defense and immune recruitment. Monocyte subpopulations displayed a broader activation profile than microglia and was a central mediator of crosstalk between immune cells. Cytokines from microglia, monocytes, and T cells reprogrammed brain cells, notably endothelial cells and oligodendrocytes, disrupting brain functions. Comparing datasets from various brain diseases revealed the identified microglia subpopulation as specific to viral infections. Conclusions This study identifies a unique population of virus-activated microglia with antiviral and proinflammatory properties and reveals monocytes to be a key driver of interactions driving pathology in the virus-infected brain.